2018
DOI: 10.7897/2230-8407.099185
|View full text |Cite
|
Sign up to set email alerts
|

The Third-Generation Cephalosporin Use in a Regional General Hospital in Indonesia

Abstract: Antibiotic is used abundantly over time. This study aimed to determine the profile of the use of antibiotics in units of DDD/100 bed-days, types of bacteria as well as the sensitivity of bacteria in the Surgery, Obstetrics and Gynecology, and Medical Ward of Bangil Regional General Hospital, Pasuruan in 2016. The study was conducted using a descriptive, cross-sectional study design and data collection was done retrospectively. The results showed that the most-used antibiotics in surgery and medical wards are t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…The study by Van Limburg et al showed that 88% of educational hospitals and 73% of non-educational hospitals implement antibiotic formulary for antibiotic stewardship program [ 25 ]. Guidelines for Antibiotic Use is a guideline according to the types of infections in patients or as prophylaxis for surgery [ 27 , 28 ]; therefore an ARCP can assist in the selection of antibiotics. According to the IDSA's guideline, the development of Guidelines for Antibiotic Use from recent literature and antibiotic resistance reports is an additional component for implementing antibiotic stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Van Limburg et al showed that 88% of educational hospitals and 73% of non-educational hospitals implement antibiotic formulary for antibiotic stewardship program [ 25 ]. Guidelines for Antibiotic Use is a guideline according to the types of infections in patients or as prophylaxis for surgery [ 27 , 28 ]; therefore an ARCP can assist in the selection of antibiotics. According to the IDSA's guideline, the development of Guidelines for Antibiotic Use from recent literature and antibiotic resistance reports is an additional component for implementing antibiotic stewardship.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from its effectiveness, antibiotics also carry a microbial resistance risk. Unnecessary antibiotic prescription is the most common sign of inappropriate antibiotic use [23][24][25][26][27]. Antibiotics should not be carelessly prescribed for acute gastroenteritis since the misuse of antibiotics contributes to antibiotic resistance, one of which is Clostridium difficile infection.…”
Section: Discussionmentioning
confidence: 99%
“…It is stated in their WHO report on surveillance of antibiotic consumption that the incidence of antibiotic resistance has increased rapidly in Asia, with the highest incidence in Southeast Asia [2,3]. Overprescribing [4], and the use of monotherapy broad-spectrum antibiotics [5,6] are the main causes of antibiotic resistance [7,8]. The reasons for antibiotic overprescribing and the use of monotherapy broad-spectrum antibiotics are the massive antibiotics revenue [9,10], the lack of supervision in antibiotic distribution by the regulatory authorities [11], physician-related factors, and patient-related factors [12].…”
Section: Introductionmentioning
confidence: 99%